Hydration dependent studies of highly aligned multilayer lipid membranes by neutron scattering - Trapp, Marcus; Gutberlet, Thomas; Juranyi, Fanni; Unruh, Tobias; Demé, Bruno; Tehei, Moeava; Peters, Judith (Journal of Chemical Physics, 2010)
We investigated molecular motions on a picosecond timescale of 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) model membranes as a function of hydration by using elastic and quasielastic neutron scattering. Two different hydrations corresponding to approximately nine and twelve water molecules per lipid were studied, the latter being the fully hydrated state. In our study, we focused on head group motions by using chain deuterated lipids. Information on in-plane and out-of-plane motions could be extracted by using solid supported DMPC multilayers. Our studies confirm and complete former investigations by Konig et al. [J. Phys. II (France) 2, 1589 (1992)] and Rheinstadter et al. [Phys. Rev. Lett. 101, 248106 (2008)] who described the dynamics of lipid membranes, but did not explore the influence of hydration on the head group dynamics as presented here. From the elastic data, a clear shift of the main phase transition from the P-beta ripple phase to the L-alpha liquid phase was observed. Decreasing water content moves the transition temperature to higher temperatures. The quasielastic data permit a closer investigation of the different types of head group motion of the two samples. Two different models are needed to fit the elastic incoherent structure factor and corresponding radii were calculated. The presented data show the strong influence hydration has on the head group mobility of DMPC. (C) 2010 American Institute of Physics. [doi:10.1063/1.3495973]